Drug facilitated sexual assault with lethal outcome: GHB intoxication in a six-year-old girl. (February 2016) - Mehling, Lena-Maria; Johansen, Sys Stybe; Wang, Xin; Doberentz, Elke; Madea, Burkhard; Hess, Cornelius
Highlights: Case of drug facilitated sexual assault. A six year-old girl died after ingestion of GHB. Increased GHB concentrations in cardiac blood and hair post mortem. Confessions of the perpetrator revealed amount of given GHB and GBL. Abstract: A very serious case of DFSA (drug facilitated sexual assault) is presented, in which a six-year-old girl died following sedation with γ-hydroxybutyric acid (GHB). She had been sexually abused by a relative. Samples of cardiac blood, bile, vitreous humour, liver, kidney, brain tissues and hair were analysed by a LC–MS/MS method. The following GHB concentrations were determined: cardiac blood: 150 mg/l; bile: 292 mg/l; vitreous humour: 58 mg/l; liver: 100 mg/kg; kidney: 124.5 mg/kg, brain: 110 mg/kg. Very high GHB levels were found in the proximal part of the hair sample (about 40.9 ng/mg). In distal segments of hair – up to 12 cm distant from the hair scalp – GHB concentrations were higher than the overall found endogenous range of 2–3 ng/mg. Police investigations revealed that the uncle had also administered GHB to the older half-sister. Therefore, a sample of her hair was analysed accordingly, but unremarkable results were obtained. Comparing our toxicological results with police investigations and the offender's statements it can be assumed that the 6-year-old girl had ingested GHB. By exclusion of other causes of death a lethal intoxication with GHB could be confirmed.